Exploratory Factor Analysis of Instruments Evaluation Interactivity Learning Management System (LMS) for Increase Involvement Study Student Faculty of Engineering - Dian Pertiwi Josua; Nur Idayanti; Riyadi; Iva Sarifah; Riyan Arthur (Jurusan Teknik Informatika dan Komputer, 2025)
Digital-based learning is currently trending and continues to increase along with the development of technology. This study aims to explore the main factors underlying the interactivity of the Learning Management System (LMS) in increasing the learning engagement of students of the Faculty of Engineering; using the exploratory factor analysis (EFA) method, the LMS interactivity instrument was evaluated through a survey of 108 students. The Kaiser-Meyer-Olkin (KMO) test produced a value of 0.85, indicating perfect sample adequacy, and Bartlett's Test of Sphericity showed significant results (χ² = 456.21; p < 0.05). Four main factors were identified with a total variance of 65.9%, including: (1) active student involvement (31.2%), (2) constructivism-based learning approach (15.8%), (3) student intrinsic motivation (12.1%), and (4) ease of technology navigation (6.8%). The results of the reliability test showed a Cronbach's Alpha value > 0.70 for all factors, indicating good internal consistency. This study concluded that interactive and data-driven LMS design can significantly increase student engagement. The developed instrument is valid and reliable for measuring LMS interactivity and can be a reference for educational institutions in developing technology-based learning systems.